Solid electrolyte, active material layer, electrolyte layer and secondary battery
By adopting a specific composition of Li6-xR1-xMx(BO3)3 oxide solid electrolyte, the problems of low ion conductivity and high resistance phase formation of solid electrolyte during low temperature sintering are solved, and efficient secondary battery performance improvement is achieved.
Patent Information
- Application Number
- CN202280017142.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-01-20
- Filing Date
- 2022-02-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-02-24
AI Technical Summary
It is difficult for the existing solid electrolyte to form high ionic conductivity when sintered at low temperatures, and high resistance phases are easily formed at the interface between the solid electrolyte and the active material, which limits the performance of the secondary battery.
The oxide-based solid electrolyte with the general formula Li6-xR1-xMx(BO3)3 is adopted, wherein R is a rare earth element including Yb, Er, Ho, Tm, La, Nd and Sm, and M is a tetravalent of Zr, Ce and Sn Elements, which show specific diffraction peak positions and differences through CuKα ray X-ray diffraction analysis, adjust charge balance to improve ionic conductivity.
A high-ionic conductivity solid electrolyte sintered at low temperature is achieved, which reduces the formation of high resistance phase between the solid electrolyte and the active material, and improves the output characteristics of the secondary battery.
Smart Images

Figure CN116888688B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte, and an active material layer, an electrolyte layer and a secondary battery containing the same. Background Art
[0002] All-solid secondary batteries containing solid electrolytes can have higher heat resistance and improved safety because the electrolyte does not leak or volatilize. Therefore, module costs can be reduced and energy density can be increased.
[0003] As one of such solid electrolytes, sulfide-based solid electrolytes have been reported. However, sulfide-based solid electrolytes have problems in processability because sulfide is used as a raw material for its production. Therefore, oxide-based solid electrolytes have been reported as non-sulfide-based solid electrolytes.
[0004] As Li-containing solid electrolytes, NASICON-type Li 1+x Al x Ti 2-x (PO 4 ) 3 (LATP), perovskite-type Li 3+x La 2 / 3-x TiO 3 (LLT) and garnet-type cubic Li 7 La 3 Zr 2 O 12 As a sodium-containing solid electrolyte, β″-alumina-type Na 2 O·(5-7)Al 2 O 3 and NASICON type Na 3 Zr 2 Si 2 PO 12 . However, these solid electrolytes have the following problems: the available negative electrode materials are limited, and sintering at high temperatures above 1,000°C is required to improve conductivity by bringing the interfaces between the solid electrolytes and the interfaces between the solid electrolytes and the active materials into close contact with each other. In particular, sintering at high temperatures causes the formation of high resistance phases between the solid electrolytes and at the interfaces between the solid electrolytes and the active materials, thereby limiting the improvement of ion conductivity.
[0005] For these reasons, attempts have recently been made to lower the sintering temperature. Japanese Patent Laid-Open No. 5-54712 discloses that by using a sintering process containing lithium borate such as Li 2+x C l-x B x O 3The solid electrolyte can reduce the post-calcination temperature to about 900°C.
[0006] Japanese Patent Laid-Open No. 2013-37992 states that when forming a solid electrolyte, Li 3 BO 3 Mixing with LLZ-type oxides can reduce the sintering temperature to 650°C to 800°C.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Laid-Open No. 5-54712
[0010] Patent Document 2: Japanese Patent Laid-Open No. 2013-37992 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] In secondary batteries containing the respective solid electrolytes disclosed in Japanese Patent Laid-Open Nos. 5-54712 and 2013-37992, a lower sintering temperature is used, and a high resistance phase as an intermediate layer is not easily formed at the interface with other materials. However, in some cases, the ionic conductivity σ of the region occupied by each solid electrolyte at room temperature is SE Less than 1×10 -7 S / cm. There is a need for oxide-based solid electrolytes with enhanced ionic conductivity.
[0013] An object of the present invention is to provide a solid electrolyte having high ion conductivity which can be produced by sintering at a low temperature, and an electrolyte layer, an active material layer, and a secondary battery comprising the solid electrolyte.
[0014] Solutions for solving problems
[0015] The solid electrolyte according to an embodiment of the present invention comprises a 6-x R 1-x M1 x (BO 3 ) 3 Represents oxide.
[0016] However, R is at least one or two elements selected from the group consisting of trivalent elements Yb, Er, Ho, and Tm, M1 is a tetravalent element, and x is a real number satisfying 0 < x < 1. The solid electrolyte according to an embodiment of the present invention includes a boron oxide containing Li, an element R selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and an element M selected from the group consisting of Zr, Ce, and Sn.
[0017] The solid electrolyte according to an embodiment of the present invention includes a boron oxide containing Li, an element R selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and an element M selected from the group consisting of Zr, Ce, and Sn, wherein the solid electrolyte shows two diffraction peaks in the range where the diffraction angle 2θ is 27.4° or more and 29.0° or less in X-ray diffraction analysis using CuKα rays, and the difference in diffraction angle 2θd between the higher angle diffraction peak and the lower angle diffraction peak is 0.43° or more.
[0018] The solid electrolyte according to an embodiment of the present invention contains an oxide represented by the general formula Li 6-x R 1-x M x (BO 3 ) 3 In this formula, R contains rare earth elements selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm and is at least one or two elements, M is a tetravalent element, and x is a real number satisfying 0 < x < 1. The solid electrolyte contains an oxide represented by the general formula Li 6-x R 1-x M x (BO 3 ) 3 In this formula, R is a rare earth element selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, M is an element selected from the group consisting of Zr, Ce, and Sn, and x is a real number satisfying 0 < x < 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a graph showing the relationship between the ionic conductivity of each of the solid electrolytes included in Example 1 to 12 according to the first embodiment and the value of the composition x (x1 + x2) of the substitution element M.
[0020] Figure 2 shows the diffraction curves of the solid electrolytes according to Examples 1 to 12.
[0021] Figure 3 shows the diffraction curves of the solid electrolytes according to Examples 1 to 6.
[0022] Figure 4 Shows the diffraction curves of solid electrolytes according to Embodiments 7 to 10.
[0023] Figure 5A Is a schematic cross-sectional view of a secondary battery according to a second embodiment.
[0024] Figure 5B Is a partially enlarged view of a positive electrode and an electrolyte layer according to a second embodiment.
[0025] Fig. 6A Is a graph showing the relationship between the ionic conductivity of each solid electrolyte according to Embodiments 13 to 33 included in the first embodiment and the value of the composition x (x1 + x2) of the substitution element M.
[0026] Figure 6B Is a graph showing the relationship between the ionic conductivity of each solid electrolyte according to Embodiments 1 to 12 included in the first embodiment and the value of the composition x (x1 + x2) of the substitution element M.
[0027] Figure 7 Is a graph showing the relationship between the ionic conductivity of solid electrolytes according to Embodiments 1 to 33, Comparative Examples 1 to 5, and Reference Examples 1 to 3 included in the first embodiment and the value of the composition x (x1 + x2) of the substitution element M. Detailed Description of the Embodiments
[0028] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0029] (First Embodiment)
[0030] The solid electrolyte according to this embodiment contains an oxide represented by the general formula Li 6-x R 1-x M1 x (BO 3 ) 3 Indicates.
[0031] In this formula, R is at least one or two elements selected from the group including the trivalent elements Yb, Er, Ho, and Tm, and M1 is a tetravalent element. In this formula, x is a real number satisfying 0 < x < 1.
[0032] In this formula, when R contains at least two elements selected from the group including the trivalent elements Yb, Er, Ho, and Tm, a combination of elements selected from the group including Yb, Er, Ho, and Tm can be used, and a combination of other trivalent elements with similar ionic radii to these elements can also be used.
[0033] In other words, the solid electrolyte according to this embodiment contains an oxide represented by the general formula Li 6-x R 1-x Mx (BO 3 ) 3 The oxide represented.
[0034] In this formula, R is at least one or two rare earth elements selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and M is an element selected from the group consisting of Zr, Ce, and Sn. In this formula, x is a real number satisfying 0 < x < 1.
[0035] In this formula, when R contains at least two elements selected from the group consisting of the rare earth elements Yb, Er, Ho, Tm, La, Nd, and Sm, combinations of the rare earth elements in this group can be used, and combinations of other rare earth elements with similar ionic radii to these elements can also be used.
[0036] The possible reasons for the improvement of the ionic conductivity of the solid electrolyte containing the oxide represented by the above general formula will be described below.
[0037] When the rare earth elements Yb, Er, Ho, Tm, La, Nd, and Sm are partially replaced by the tetravalent element M, the charge balance is adjusted in such a way that the whole crystal is neutral, thereby creating a state of Li + deficiency. The part lacking an element is usually called a vacancy. The Li + around the vacancy moves to the vacancy (usually called hopping) in a coordinated manner, thereby improving the ionic conductivity.
[0038] In other words, the solid electrolyte of the present embodiment is a solid electrolyte including a boron oxide containing Li, an element R selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and an element M selected from the group consisting of Zr, Ce, and Sn.
[0039] The solid electrolyte of the present embodiment preferably has a monoclinic crystal structure.
[0040] In X-ray diffraction analysis using CuKα radiation (hereinafter referred to as "XRD"), the diffraction peak at a diffraction angle 2θ of about 28° varies according to the composition of the solid electrolyte.
[0041] In the present embodiment, the solid electrolyte in which R in the oxide represented by the general formula Li 6-x R 1-x M x (BO 3 ) 3 is Yb preferably shows a diffraction peak in the range of 2θ = 28.07° or more and 28.20° or less in XRD using CuKα radiation. More preferably, the solid electrolyte has a peak in the range of 2θ = 28.10° or more and 28.20° or less.
[0042] In the solid electrolyte of the present embodiment, in which R in the oxide represented by the general formula Li 6-x R 1-x M x (BO 3 ) 3 is Er, it preferably shows a diffraction peak in the range of 2θ = 27.94° or more and 28.10° or less in XRD using CuKα rays. More preferably, the solid electrolyte has a peak in the range of 2θ = 28.0° or more and 28.20° or less.
[0043] In XRD using CuKα rays, the position of the diffraction peak at about 2θ = 28° can be controlled by adjusting the value of x in the general formula and changing the element represented by M.
[0044] M in the above general formula is a tetravalent element. M is at least one element selected from the group including Zr, Ce, and Sn.
[0045] As an element for substituting Yb, Er, Ho, Tm, La, Nd, and Sm as trivalent elements R, elements with similar ionic radii are likely to substitute for them. Specific examples thereof include Zr 4+ , Ce 4+ , Sn 4+ , Ti 4+ , Nb 4+ , Pb 4+ , Pr 4+ , and Nb 5+ as candidates. Among them, Zr 4+ and Ce 4+ are more likely to substitute.
[0046] In the above general formula, x is a real number satisfying 0 < x < 1. As x corresponding to the amount of the substituting element M for the element R, a value of 0.025 or more and 0.600 or less is used. More preferably, a value of 0.075 or more and 0.400 or less is used.
[0047] The reason for preferably using the above x range is inferred as follows: When the value of x is less than 0.025, since the substitution amount of the element R is small, sufficient structural changes do not occur, and the path through which ions pass is not sufficiently formed, resulting in no improvement in ionic conductivity. When the value of x is greater than 0.600, the amount of the substituting element M is too large. Therefore, the excessive element M that does not contribute to the substitution of the element R in the crystal contributes as an ion conduction inhibiting component rather than the substitution effect in the crystal.
[0048] Next, the production method of the solid electrolyte of the present embodiment will be described.
[0049] The method for producing the solid electrolyte of the present embodiment comprises heating a solid electrolyte having a composition of the general formula Li 6-x R 1-x M x (BO 3 ) 3 (wherein in the formula, R is at least one or two elements selected from the group consisting of rare earth elements Yb, Er, Ho, Tm, La, Nd and Sm, and M is a tetravalent element) of a solid electrolyte of an oxide represented by the elements Li, R and M, or a post-calcination step of their oxides.
[0050] The method for producing a solid electrolyte of the present embodiment includes a pre-baking step of performing a heat treatment at a temperature lower than the melting point of the oxide to perform solid phase synthesis of the oxide represented by the above general formula, and a step of densifying the obtained oxide by the heat treatment.
[0051] Although a method for producing the solid electrolyte of the present embodiment including the pre-baking step and the post-baking will be described in detail below, the present invention is not limited to the following production method.
[0052] <Pre-baking step>
[0053] In the pre-calcination step, the reagent grade raw materials, such as Li 3 BO 3 , H 3 BO 3 , Yb 2 O 3 , Er 2 O 3 、Ho 2 O 3 、Tm 2 O 3 、ZrO 2 and CeO 2 , and mixed together to form Li 6-x R 1-x M x (BO 3 ) 3 Other raw materials weighed to achieve a predetermined stoichiometric ratio include SnO 2 , Nb 2 O 3 ,La 2 O 3 、Nd 2 O 3 and Sm 2 O 3Here, R is at least one or two elements selected from the group consisting of rare earth elements Yb, Er, Ho, Tm, La, Nd, and Sm. As M, a tetravalent element is used.
[0054] As a device for mixing, in addition to a mortar and pestle, a mixer such as a ball mill can also be used.
[0055] After preparing the mixed powder of the above-mentioned raw materials by mixing treatment, the obtained mixed powder is press-formed into pellets. Here, as a press-forming method, a known press-forming method such as cold uniaxial forming method or cold isostatic pressing method can be used. As a condition for press-forming in the pre-baking step, the pressure can be, but is not particularly limited to, for example, 100 to 300 MPa.
[0056] The obtained pellets are pre-baked at 500 to 800° C. using, for example, an atmospheric calcination apparatus to perform solid phase synthesis. The time of the pre-baking step may be, but is not particularly limited to, for example, about 700 to 750 minutes (eg, 720 minutes).
[0057] The obtained pre-calcined body is composed of the general formula Li 6-x R 1-x M x (BO 3 ) 3 The pre-baked body may be ground with, for example, a mortar and pestle to prepare a pre-baked powder.
[0058] <Post-calcination step>
[0059] In the post-baking step, at least one selected from the group consisting of the pre-baked body and the pre-baked powder prepared in the pre-baking step is pressure-formed and post-baked to prepare a dense sintered body.
[0060] The press forming and post-baking can be performed simultaneously by, for example, spark plasma sintering or hot pressing. Alternatively, after the pellets are produced by cold uniaxial forming, post-baking can be performed, for example, in an atmospheric atmosphere. As a condition for press forming in the post-baking step, the pressure can be, but is not particularly limited to, for example, 100 to 300 MPa.
[0061] The post-calcination temperature is preferably 800° C. or lower, more preferably 700° C. or lower, still more preferably 680° C. or lower.
[0062] The time of the post-baking step may be appropriately changed depending on, for example, the temperature of the post-baking, and may be, for example, about 700 to 750 minutes (eg, 720 minutes).
[0063] The cooling method in the post-calcination step is not particularly limited. Natural cooling may be used. Cooling slower than natural cooling may also be used.
[0064] Next, the secondary battery of the present embodiment will be described.
[0065] A typical secondary battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, an electrolyte including a solid electrolyte provided between the positive electrode and the negative electrode, and a current collector as needed.
[0066] The secondary battery of the present embodiment is a secondary battery including at least a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material and an electrolyte, and at least one selected from the group including a positive electrode, a negative electrode and an electrolyte includes the solid electrolyte of the present embodiment.
[0067] In the secondary battery of the present embodiment, the electrolyte may include the solid electrolyte of the present embodiment, or may include other solid electrolytes. Examples of other solid electrolytes that may be included include, but are not particularly limited to, Li 3 PO 4 , Li 7 La 3 Zr 2 O 12 , Li 0.33 La 0.55 TiO 3 and Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 The solid electrolyte of the present embodiment is contained in the electrolyte of the secondary battery of the present embodiment in an amount of preferably 25% by mass or more, more preferably 50% by mass or more, still more preferably 75% by mass or more, particularly preferably 100% by mass.
[0068] The secondary battery of the present embodiment can be produced by known methods, such as by lamination, forming and heat treatment of the positive electrode, solid electrolyte and negative electrode. The solid electrolyte of the present embodiment can be produced by heat treatment at a lower temperature than conventional technology, thereby reducing the formation of a high resistance phase caused by the reaction between the solid electrolyte and the electrode active material. This can obtain a secondary battery with excellent output characteristics. The "solid" used in this specification includes an object that has a self-supporting property to the extent that it maintains a certain shape and volume even if the posture of the object changes. In other words, the object is non-flowable and has a viscosity of less than 1×10 7 cP(less than 1×10 4 Pa·s).
[0069] The measurement method of physical properties according to the present disclosure will be described below.
[0070] Identification of R and M
[0071] When the collected sample is not a mixture with other materials, after the collected sample is processed into a solution, the composition ratio of the sample can be identified by, for example, inductively coupled high-frequency plasma atomic emission spectroscopy (ICP-AES) or wavelength dispersive X-ray fluorescence spectroscopy (WDXRF). WDXRF may also be referred to as WDX.
[0072] When the possibility that the collected sample is a mixture is high, a scanning analyzer such as an X-ray photoelectron spectrometer (XPS, ESCA) or a scanning electron microscope equipped with an energy dispersive X-ray fluorescence analyzer (EDXRF) that can provide an element mapping image can be used. In the following, a scanning electron microscope equipped with an energy dispersive X-ray fluorescence spectrometer (EDXRF) can be abbreviated as SEM / EDX. When the possibility that the collected sample is a mixture is high, a transmission electron microscope (TEM-ED) equipped with an electron beam diffraction function can be used to identify the crystal structure. EDXRF can also be referred to as EDX.
[0073] ICP-AES and XPS are used to accurately determine the composition ratio of Li as a light element and other elements having a higher atomic number such as B, O, Zr, and rare earth elements.
[0074] When the collected sample is a mixture, pretreatment is used to selectively remove non-target parts for analysis by physical removal processes such as slicing or ion beam treatment, chemical removal such as dry etching or wet etching, or a combination thereof. For pretreatment, washing, degreasing, cutting, grinding, or granulation can be used.
[0075] As an analyzer for SEM / EDX, S-4800 available from Hitachi High-Technologies Corporation can be used.
[0076] Measurement of X-ray diffraction peaks
[0077] RINT-2100 available from Rigaku Corporation was used for X-ray diffraction analysis of the solid electrolyte.
[0078] The powder prepared by grinding the solid electrolyte with a mortar and pestle was subjected to X-ray diffraction analysis using characteristic X-rays of CuKα. The temperature was room temperature, the analysis range was 10° to 70°, the step length was 0.016°, and the scanning speed was 0.5 step length / second.
[0079] (Second embodiment)
[0080] <Structure of Secondary Battery and Positive Electrode>
[0081] Reference Figure 5A and Figure 5BThe electrolyte layer 40 including the solid electrolyte 44 according to the first embodiment and the secondary battery 100 including the electrolyte layer 40 are described.
[0082] Figure 5A Schematic cross-sectional view of a secondary battery 100 including an electrolyte layer 40 in which the solid electrolyte 44 of the present embodiment is used. The secondary battery 100 includes an electrolyte layer 40 on a surface of a positive electrode collector layer 10 of a positive electrode active material layer 20 on the opposite side of the positive electrode active material layer 20 in contact with the positive electrode active material layer 20. The secondary battery 100 includes a negative electrode 70 on the opposite side of the electrolyte layer 40 where the electrolyte layer 40 is in contact with the positive electrode active material layer 20. The negative electrode 70 includes a negative electrode active material layer 50 on the opposite surface of the surface of the electrolyte layer 40 in contact with the positive electrode active material layer 20. The negative electrode 70 includes a negative electrode collector layer 60 on the opposite surface of the surface of the negative electrode active material layer 50 in contact with the electrolyte layer 40. In other words, the secondary battery 100 includes a negative electrode 70, an electrolyte layer 40, and a positive electrode 30 in a stacking direction 200.
[0083] like Figure 5B As shown, an electrolyte layer 40 using an electrolyte 44 of the present embodiment is in contact with a positive electrode 30, and the positive electrode 30 includes a positive electrode collector layer 10 and a positive electrode active material layer 20 containing active material particles 22 and a positive electrode electrolyte 24. In this specification, a structure configured to transfer lithium ions (active material ions) with the electrolyte layer 40 is referred to as a positive electrode; therefore, the positive electrode active material layer 20, which is a part of the positive electrode 30 other than the positive electrode collector layer 10, may also be referred to as a positive electrode 20, such as Figure 5A The positive electrode active material layer 20 of the present embodiment includes a positive electrode electrolyte 24 , and thus may be referred to as a composite positive electrode active material layer 20 or a composite positive electrode structure 20 .
[0084] The collector layer 10 is a conductor that conducts electrons to or from an external circuit (not shown) and an active material layer. As the collector layer 10, a self-supporting film of a metal such as stainless steel (SUS) or aluminum, or a laminated structure of a metal foil and a resin substrate is used.
[0085] The positive electrode active material layer 20 includes positive electrode active material layers 20a, 20b and 20c as sublayers. Before sintering the active material particles 22 and the positive electrode electrolyte 24, the positive electrode active material layers 20a, 20b and 20c are distinguished by stacking units in the layer thickness direction 200. The positive electrode active material layers 20a, 20b and 20c may have a distribution in the layer thickness direction in terms of the volume fraction of the active material particles 22 and the positive electrode electrolyte 24, the conductive aid (not shown) and the void ratio (porosity). The layer thickness direction 200 is parallel or anti-parallel to the stacking direction of the stacked layers, and therefore may also be referred to as the stacking direction 200.
[0086] The solid electrolyte 44 according to the present embodiment is used for the positive electrode electrolyte 24 in the composite positive electrode active material layer 20. The positive electrode electrolyte 24 and the solid electrolyte 44 in the electrolyte layer 40 may have the same composition and particle size distribution, or may have different compositions and particle size distributions.
[0087] (negative electrode)
[0088] As a method for producing the negative electrode, a known method can be used. As in the second embodiment of the present application, the method for producing the positive electrode 30 in the first embodiment can be used for the formation of the negative electrode by necessary changes. Similar to the positive electrode 30, the negative electrode may have a structure in which both the negative electrode active material and the solid electrolyte are contained in a layer, or may be formed of a film composed of a metal such as metal Li or In-Li.
[0089] [Negative electrode active material]
[0090] Examples of negative electrode active materials include metals, metal fibers, carbon materials, oxides, nitrides, silicon, silicon compounds, tin, tin compounds, and various alloy materials. Among them, from the viewpoint of capacity density, metals, oxides, carbon materials, silicon, silicon compounds, tin, and tin compounds are preferred. Examples of metals include metal Li and In-Li. Examples of oxides include Li 4 Ti 5 O 12 (lithium titanate: LTO). Examples of carbon materials include various natural graphites (graphites), coke, graphitizable carbon materials that undergo graphitization, carbon fibers, spherical carbon, various artificial graphites, and amorphous carbon. Examples of silicon compounds include silicon-containing alloys, silicon-containing inorganic compounds, silicon-containing organic compounds, and solid solutions. Examples of tin compounds include SnO b (0 <b<2)、SnO 2 、SnSiO 3 、Ni 2 Sn 4 and Mg 2 Sn. The negative electrode material may contain a conductive aid. Examples of conductive aids include graphites such as natural graphite and artificial graphite, and carbon blacks such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black. Other examples of conductive aids include conductive fibers such as carbon fibers, carbon nanotubes, and metal fibers, carbon fluorides, metal powders such as aluminum, conductive metal oxides such as conductive whiskers such as zinc oxide and titanium oxide, and organic conductive materials such as phenylene-based dielectrics.
[0091] Example
[0092] An example of production and evaluation of the solid electrolyte of the present embodiment as a sintered body will be described. The present disclosure is not limited to the following examples.
[0093] [Example 1]
[0094] <Pre-baking step>
[0095] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.975 Yb 0.975 Zr 0.025 (BO 3 ) 3 , and mix using a mortar and pestle.
[0096] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0097] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0098] <Post-calcination step>
[0099] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 1. The heating temperature was 670° C., and the holding time was 720 minutes.
[0100] [Examples 2 to 4]
[0101] <Pre-baking step>
[0102] A pre-calcined body and a pre-calcined powder were produced in the same manner as in Example 1, except that each raw material described in Example 1 was weighed at a predetermined stoichiometric ratio in such a manner that x had a value given in Table 1.
[0103] <Post-calcination step>
[0104] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body.
[0105] [Example 5]
[0106] <Pre-baking step>
[0107] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.), and CeO 2 (obtained from Iwatani Corporation) as a raw material for the solid electrolyte. In addition to weighing in a predetermined stoichiometric ratio, the composition after sintering is Li 5.875 Yb 0.875 Zr 0.100 Ce 0.025 (BO 3 ) 3 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except for the above.
[0108] <Post-calcination step>
[0109] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body. The heating temperature was 650° C., and the holding time was 720 minutes.
[0110] [Example 6]
[0111] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.), and CeO 2(obtained from Iwatani Corporation) as a raw material for the solid electrolyte. In addition to weighing in a predetermined stoichiometric ratio, the composition after sintering is Li 5.850 Yb 0.850 Zr 0.100 Ce 0.050 (BO 3 ) 3 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except for the above.
[0112] <Post-calcination step>
[0113] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body. The heating temperature was 670° C., and the holding time was 720 minutes.
[0114] [Example 7]
[0115] <Pre-baking step>
[0116] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Er 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.975 Er 0.975 Zr 0.025 (BO 3 ) 3 , and mix using a mortar and pestle.
[0117] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0118] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0119] <Post-calcination step>
[0120] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 7. The heating temperature was 670° C., and the holding time was 720 minutes.
[0121] [Examples 8 to 10]
[0122] <Pre-baking step>
[0123] A pre-calcined body and a pre-calcined powder were produced in the same manner as in Example 7, except that each raw material described in Example 7 was weighed at a predetermined stoichiometric ratio in such a manner that x had a value given in Table 1.
[0124] <Post-calcination step>
[0125] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body.
[0126] [Example 11]
[0127] <Pre-baking step>
[0128] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Ho 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Ho 0.900 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0129] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0130] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0131] <Post-calcination step>
[0132] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 11. The heating temperature was 650° C., and the holding time was 720 minutes.
[0133] [Example 12]
[0134] <Pre-baking step>
[0135] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Tm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Tm 0.900 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0136] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0137] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0138] <Post-calcination step>
[0139] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 12. The heating temperature was 670° C., and the holding time was 720 minutes.
[0140] [Comparative Example 1]
[0141] <Pre-baking step>
[0142] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3(obtained from Kishida Chemical Co., Ltd.) and Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.) as a raw material for the solid electrolyte. In addition to weighing in a predetermined stoichiometric ratio, the composition after sintering is Li 6 Yb(BO 3 ) 3 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except for the above.
[0143] <Post-calcination step>
[0144] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body. The heating temperature was 670° C., and the holding time was 720 minutes.
[0145] [Comparative Example 2]
[0146] <Pre-baking step>
[0147] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), and Er 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.) as a raw material for the solid electrolyte. In addition to weighing in a predetermined stoichiometric ratio, the composition after sintering is Li 6 Er(BO 3 ) 3 A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1 except for the above.
[0148] <Post-calcination step>
[0149] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body. The heating temperature was 670° C., and the holding time was 720 minutes.
[0150] [Reference Example 1]
[0151] <Pre-baking step>
[0152] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Nd 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Nd 0.900 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0153] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0154] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0155] <Post-calcination step>
[0156] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Reference Example 1. The heating temperature was 650° C., and the holding time was 720 minutes.
[0157] [Reference Example 2]
[0158] <Pre-baking step>
[0159] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Sm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Sm 0.900 Zr 0.100 (BO 3) 3 , and mix using a mortar and pestle.
[0160] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0161] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0162] <Post-calcination step>
[0163] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Reference Example 2. The heating temperature was 650° C., and the holding time was 720 minutes.
[0164] Composition analysis and X-ray diffraction peak measurement were performed on the sintered bodies of Examples 1 to 12, Comparative Examples 1 and 2, and Reference Examples 1 and 2 by the above method. Ionic conductivity was measured by the following method. The measurement method of ionic conductivity is described below. Table 1 shows the evaluation results obtained.
[0165] Measurement of ionic conductivity
[0166] Gold electrodes were deposited on the top and bottom surfaces of each flat sintered body obtained by the post-baking step using a magnetron sputtering system MSP-10 available from Vacuum Device Co., Ltd. to produce samples for AC impedance measurement.
[0167] A potentiostat / galvanostat SI 1287A and a frequency response analyzer 1255b from Solartron Analytical were used for the AC impedance measurements. The measurement conditions were room temperature and a frequency of 1 MHz to 0.1 Hz.
[0168] The resistance of the sintered body was calculated from the complex impedance diagram obtained by the impedance measurement. The ion conductivity was determined using the following formula from the calculated resistance, the thickness of the sintered body and the electrode area.
[0169] Ionic conductivity (S / cm) = sintered body thickness (cm) / (sintered body resistance (Ω) × electrode area (cm) 2 ))
[0170] [Examples 13 and 14]
[0171] <Pre-baking step>
[0172] Provide Li 3 BO 3(obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Tm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Yb 0.720 Tm 0.180 Zr 0.100 (BO 3 ) 3 and Li 5.800 Yb 0.640 Tm 0.160 Zr 0.200 (BO 3 ) 3 , and mix using a mortar and pestle.
[0173] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0174] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0175] <Post-calcination step>
[0176] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce sintered bodies of Examples 13 and 14. The heating temperature was 670° C., and the holding time was 720 minutes.
[0177] [Example 15]
[0178] <Pre-baking step>
[0179] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3(obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Tm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.), and CeO 2 (obtained from Iwatani Corporation) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.875 Yb 0.700 Tm 0.175 Zr 0.100 Ce 0.025 (BO 3 ) 3 , and mix using a mortar and pestle.
[0180] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0181] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0182] <Post-calcination step>
[0183] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 15. The heating temperature was 670° C., and the holding time was 720 minutes.
[0184] [Examples 16 and 17]
[0185] <Pre-baking step>
[0186] A pre-calcined body and pre-calcined powder were produced in the same manner as in Example 15, except that the raw materials described in Example 15 were weighed in a predetermined stoichiometric ratio so that R1, R2, R1 ratio, R2 ratio, M1 component and x=x1+x2 had the values given in Table 2.
[0187] <Post-calcination step>
[0188] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 15 to produce a sintered body.
[0189] [Example 18]
[0190] <Pre-baking step>
[0191] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Nd 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Yb 0.720 Nd 0.180 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0192] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0193] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0194] <Post-calcination step>
[0195] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 18. The heating temperature was 670° C., and the holding time was 720 minutes.
[0196] [Examples 19 to 21]
[0197] <Pre-baking step>
[0198] A pre-calcined body and pre-calcined powder were produced in the same manner as in Example 18, except that the raw materials described in Example 18 were weighed in a predetermined stoichiometric ratio so that R1, R2, R1 ratio, R2 ratio, M1 component and x=x1+x2 had the values given in Table 2.
[0199] <Post-calcination step>
[0200] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 18 to produce a sintered body.
[0201] [Examples 22 and 23]
[0202] <Pre-baking step>
[0203] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Nd 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.) and CeO 2 (obtained from Iwatani Corporation) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.875 Yb 0.788 Nd 0.088 Zr 0.100 Ce 0.025 (BO 3 ) 3 and Li 5.875 Yb 0.700 Nd 0.175 Zr 0.100 Ce 0.025 (BO 3 ) 3 The weighed ingredients were stirred and mixed using a mortar and pestle.
[0204] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0205] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0206] <Post-calcination step>
[0207] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce sintered bodies of Examples 22 and 23. The heating temperature was 670° C., and the holding time was 720 minutes.
[0208] [Example 24]
[0209] <Pre-baking step>
[0210] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Er 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.800 Yb 0.640 Er 0.160 Zr 0.200 (BO 3 ) 3 , and mix using a mortar and pestle.
[0211] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0212] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0213] <Post-calcination step>
[0214] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 24. The heating temperature was 670° C., and the holding time was 720 minutes.
[0215] [Example 25]
[0216] <Pre-baking step>
[0217] Provide Li3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Sm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Yb 0.810 Sm 0.090 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0218] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0219] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0220] <Post-calcination step>
[0221] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 25. The heating temperature was 670° C., and the holding time was 720 minutes.
[0222] [Example 26]
[0223] <Pre-baking step>
[0224] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3(obtained from Kojundo Chemical Laboratory Co., Ltd.), La 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and ZrO 2 (obtained from Nippon Denko Co., Ltd.) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.900 Yb 0.810 La 0.090 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0225] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0226] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0227] <Post-calcination step>
[0228] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 26. The heating temperature was 670° C., and the holding time was 720 minutes.
[0229] [Example 27]
[0230] <Pre-baking step>
[0231] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), La 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.), and CeO 2(obtained from Iwatani Corporation) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.88 Yb 0.788 La 0.088 Zr 0.100 Ce 0.025 (BO 3 ) 3 , and mix using a mortar and pestle.
[0232] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0233] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0234] <Post-calcination step>
[0235] The pre-calcined powder prepared as described above was formed and heat-treated in the same manner as in the pre-calcination to produce a sintered body of Example 27. The heating temperature was 670° C., and the holding time was 720 minutes.
[0236] [Examples 28 and 29]
[0237] <Pre-baking step>
[0238] A pre-calcined body and pre-calcined powder were produced in the same manner as in Example 27, except that the raw materials described in Example 27 were weighed in a predetermined stoichiometric ratio so that R1, R2, R1 ratio, R2 ratio, M1 component and x=x1+x2 had the values given in Table 2.
[0239] <Post-calcination step>
[0240] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 27 to produce a sintered body.
[0241] [Comparative Examples 3 to 5]
[0242] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Yb 2 O 3(obtained from Kojundo Chemical Laboratory Co., Ltd.), Tm 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), Nd 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), and La 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.) as a raw material for the solid electrolyte.
[0243] <Pre-baking step>
[0244] A pre-calcined body and pre-calcined powder were produced in the same manner as in Example 13, except that the raw materials described in Example 13 were weighed in a predetermined stoichiometric ratio so that R1, R2, R1 ratio, R2 ratio, M1 component and x=x1+x2 had the values given in Table 2.
[0245] <Post-calcination step>
[0246] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 13 to produce a sintered body.
[0247] [Example 30]
[0248] <Pre-baking step>
[0249] Provide Li 3 BO 3 (obtained from Toshima Manufacturing Co., Ltd.), H 3 BO 3 (obtained from Kishida Chemical Co., Ltd.), Er 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), La 2 O 3 (obtained from Kojundo Chemical Laboratory Co., Ltd.), ZrO 2 (obtained from Nippon Denko Co., Ltd.), and CeO 2 (obtained from Iwatani Corporation) as the raw material of the solid electrolyte. They were weighed in a predetermined stoichiometric ratio so that the composition after sintering was Li 5.9 Er0.81 La 0.090 Zr 0.100 (BO 3 ) 3 , and mix using a mortar and pestle.
[0250] Thereafter, the mixed powder was subjected to cold uniaxial forming using a hydraulic press SSP-10A available from Shimadzu Corporation, and heat-treated in an air atmosphere. The heating temperature was 650° C., and the holding time was 720 minutes.
[0251] The obtained pre-calcined body was ground with a mortar and pestle to prepare a pre-calcined powder.
[0252] <Post-calcination step>
[0253] The pre-baked powder prepared as described above was formed and heat-treated in the same manner as in the pre-baking to produce a sintered body of Example 30. The heating temperature was 670° C., and the holding time was 720 minutes.
[0254] [Examples 31 to 33]
[0255] <Pre-baking step>
[0256] A pre-calcined body and a pre-calcined powder were produced in the same manner as in Example 1, except that the respective raw materials described in Example 1 were weighed at a predetermined stoichiometric ratio so that x had a value given in Table 2.
[0257] <Post-calcination step>
[0258] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body.
[0259] [Reference Example 3]
[0260] <Pre-baking step>
[0261] A pre-calcined body and a pre-calcined powder were prepared in the same manner as in Example 1, except that the respective raw materials described in Example 1 were weighed at a predetermined stoichiometric ratio so that x had a value given in Table 2.
[0262] <Post-calcination step>
[0263] The pre-calcined powder prepared as described above was subjected to the same post-calcination step as in Example 1 to produce a sintered body.
[0264] The sintered bodies of Examples 13 to 33, Comparative Examples 3 to 5, and Reference Examples 1 to 3 were subjected to composition analysis and measurement of X-ray diffraction peaks in the same manner as in Example 1. The ion conductivity was measured in the same manner as in Example 1.
[0265] ·result
[0266] Table 1 shows the stoichiometric amounts of raw materials and the heating temperature during post-calcination, the diffraction peak position and the ionic conductivity when producing the solid electrolytes according to Examples 1 to 12, Comparative Examples 1 and 2, and Reference Examples 1 and 2. Table 2 shows the stoichiometric amounts of raw materials and the heating temperature during post-calcination, the diffraction peak position and the ionic conductivity when producing the solid electrolytes according to Examples 13 to 33, Comparative Examples 3 to 5 and Reference Example 3. Fig. 6A The relationship between the ion conductivity of each of the solid electrolytes according to Examples 13 to 33 and Comparative Examples 3 to 5 included in the first embodiment and the value of the composition x (x1+x2) of the substituting element M is shown. Figure 6B The relationship between the ion conductivity of each of the solid electrolytes according to Examples 1 to 12, Comparative Examples 1 and 2, and Reference Examples 1 to 3 included in the first embodiment and the value of the composition x (x1+x2) of the substituting element M is shown. Figure 6B Essentially based on Figure 1 The same measurement data as in the examples 13 to 33 are created Fig. 6A The appearance of the matching graph. Figure 7 The relationship between the ion conductivity of each of the solid electrolytes according to Examples 1 to 33, Comparative Examples 1 to 5, and Reference Examples 1 to 3 included in the first embodiment and the value of the composition x (x1+x2) of the substituting element M is shown. Figure 7 Essentially based on Fig. 6A The measurement data and Figure 6B The measurement data.
[0267] The results of the above composition analysis show that each sintered body (solid electrolyte) has the elements of the raw materials described in Tables 1 and 2. The sintered bodies (solid electrolytes) according to Examples 1 to 33 are each a solid electrolyte that is successfully densified at a low temperature below 700° C. and exhibits high ion conductivity.
[0268] Figure 1 The relationship between the ionic conductivity of the solid electrolytes according to Examples 1 to 12 included in the present embodiment and the value of x in the general formula is shown. The value of x in the general formula corresponds to the sum of x1 and x2 given in Table 1.
[0269] Figure 2 The diffraction curves obtained by XRD in the range of 2θ=10° to 40° are shown. It can be seen that the crystal structure in each of Examples 1 to 6 is monoclinic Li 6 Yb(BO 3 ) 3 , the crystal structure in each of Examples 7 to 10 is monoclinic Li 6 Er(BO 3 ) 3, the crystal structure in Example 11 is monoclinic Li 6 Ho(BO 3 ) 3 , and the crystal structure in Example 12 is monoclinic Li 6 Tm(BO 3 ) 3 Similarly, it was confirmed from XRD measurement that the crystal structure in each of Examples 13 to 33 was a monoclinic crystal structure.
[0270] Figure 3 and Figure 4 The diffraction curve obtained by XRD in the range of 2θ=27° or more and 29° or less is shown. It can be seen that the peak positions at about 2θ=28.1° and about 28.5° in Examples 1 to 6 are shifted to a higher angle than the peak position in Comparative Example 1. The peak positions at about 2θ=28.0° and about 28.4° in Examples 7 to 10 are shifted to a higher angle than the peak position in Comparative Example 2. It is believed that these are changes in the X-ray diffraction pattern, which corresponds to changes in the crystal structure caused by replacing at least a portion of the rare earth elements Yb and Er by at least one element selected from the group including M. Similar measurements show that the peak positions of Examples 13 to 33 are also shifted to a higher angle than the peak position when x is 0. Similarly, it is believed that the changes in the X-ray diffraction pattern correspond to changes in the crystal structure caused by replacing at least a portion of the rare earth elements used by at least one element selected from the group including M.
[0271] When the ionic conductivity σ is 1×10 -7 In the solid electrolytes according to Examples 1 to 33 with a S / cm or more, as shown in Tables 1 and 2, a peak shift of the double-peak diffraction peak to a higher angle and a shift of the X-ray diffraction angle peak to a higher angle are observed. That is, it can be read that in the range of 27.4° or more and 29.0° or less, the difference 2θd between the diffraction angles of the higher angle diffraction peak observed at 28.3° to 29.0° and the lower angle diffraction peak observed at 27.4° to 28.3° increases to 0.43° or more. In other words, the solid electrolyte according to the present embodiment includes a boron oxide containing Li, an element R selected from the group including Yb, Er, Ho, Tm, La, Nd and Sm, and an element M selected from the group including Zr, Ce and Sn. In other words, the solid electrolyte of the present embodiment is an electrolyte showing two diffraction peaks within a diffraction angle 2θ range of 27.4° to 29.0° in XRD using CuKα rays, wherein the difference 2θd between the diffraction angles of the higher angle diffraction peak and the lower angle diffraction peak is 0.43° or more.
[0272] The two diffraction peaks observed within the diffraction angle 2θ range of 27.4° or more and 29.0° or less may also include a multi-peak including three peaks or four peaks depending on the crystallinity. In the present specification, the two diffraction peaks are expressed as having one peak on the lower angle side and one peak on the higher angle side adjacent to the diffraction angle 2θ of 28.3°, respectively. In this way, the diffraction peaks are separated by fitting to a double peak diffraction profile.
[0273] As the composition of the substituting element M increases or as the ionic conductivity increases, this high-angle diffraction peak becomes more significantly broadened and shifts to a higher angle than the low-angle diffraction peak. These results show that the solid electrolyte 44 of the present embodiment has a different crystal structure from the unsubstituted comparative example, so that a variety of crystal structures with lattice spacing and crystallite size distribution are mixed.
[0274] Table 2 and Fig. 6A and Figure 7 The solid electrolytes according to Examples 13 to 33 described in the drawings differ from the solid electrolytes according to Examples 1 to 12 in that the rare earth element R is binary: (Yb, Tm), (Yb, Nd), (Yb, Er), (Yb, Sm), (Yb, La) and (Er, La).
[0275] The solid electrolytes of Examples 14 to 16, 18, 22, 23 and 26 to 33 exhibit ionic conductivity of 1E-5 (S / cm) or more as in Examples 2 to 6 and 12, and can be used for the positive electrode of an all-solid battery by combining with positive electrode active material particles such as LCO to form a composite structure.
[0276] In the solid electrolytes having an ionic conductivity of 1E-7 (S / cm) or more according to Examples 1 to 33, the atomic concentration ratio [M] / [R] of the substituting element M to the rare earth element R is 0.026 or more and 1.500 or less. In the solid electrolytes having an ionic conductivity of 1E-6 (S / cm) or more according to Examples 2 to 6, 8 to 10, and 12 to 33, the atomic concentration ratio [M] / [R] of the substituting element M to the rare earth element R is 0.056 or more and 1.500 or less. In the solid electrolytes having an ionic conductivity of 2E-5 (S / cm) or more according to Examples 2 to 6, 12, 14 to 16, 18, 22, 23, 26 to 30, and 32, the atomic concentration ratio [M] / [R] of the substituting element M to the rare earth element R is 0.081 or more and 0.667 or less.
[0277] In the solid electrolytes containing multiple rare earth elements according to Examples 13 to 33, the atomic concentration ratio ([R]-[Yb]) / [R] of the solid electrolyte having an ion conductivity of 1E-5 (S / cm) or higher is 0.063 or higher and 0.200 or lower.
[0278] The atomic concentration ratio [M] / [R] of the substituent element M to the rare earth element R is expressed algebraically as [M] / [R]=(x1+x2) / (R1 ratio+R2 ratio) using the R1 ratio, R2 ratio, x1, and x2 described in Table 2. Similarly, the atomic concentration ratio [M] / [R] of the substituent element M to the rare earth element R is expressed algebraically as [M] / [R]=(x1+x2) / (1-x1-x2) using x1 and x2 described in Table 1.
[0279] The atomic concentration ratio ([R]-[Yb]) / [R] is expressed algebraically as (R2 ratio) / (R1 ratio+R2 ratio) using the R1 ratio and the R2 ratio described in Table 2.
[0280] In Table 1 and Table 2, the atomic concentration ratio [M] / [R] of the substituting element M is described as the atomic concentration ratio [M1] / [R] of the substituting element M1.
[0281] [Table 1]
[0282] Table 1
[0283]
[0284] [Table 2]
[0285] Table 2
[0286]
[0287] The present invention is not limited to the above embodiments, and various changes and modifications can be made within the spirit and scope of the present invention. Therefore, in order to disclose the scope of the present invention, the following claims are made.
[0288] This application claims priority based on Japanese Patent Application No. 2021-028807 filed on February 25, 2021, Japanese Patent Application No. 2021-101742 filed on June 18, 2021, and Japanese Patent Application No. 2022-007354 filed on January 20, 2022, the entire contents of which are incorporated herein by reference.
Claims
1. A solid electrolyte, characterized in that: It comprises the general formula Li 6-x R 1-x M1 x (BO3)3 represented by oxide, Among them, in this formula, R is a trivalent element selected from the group consisting of Yb, Er, Ho, and Tm, M1 is a tetravalent element selected from the group consisting of Zr, Ce, and Sn, and x is a real number satisfying 0 < x < 1.
2. The solid electrolyte according to claim 1, wherein The solid electrolyte exhibits two diffraction peaks in the range of 2θ = 27.4° or more and 29.0° or less in X-ray diffraction analysis using CuKα radiation, and the difference in diffraction angle 2θd between the higher-angle diffraction peak and the lower-angle diffraction peak is 0.43° or more.
3. The solid electrolyte according to claim 1, wherein R is Yb, and the solid electrolyte exhibits a diffraction peak in the range of 2θ = 28.07° or more and 28.20° or less in X-ray diffraction analysis using CuKα radiation.
4. The solid electrolyte according to any one of claims 1 to 3, wherein R is Yb, M1 is Zr, and x satisfies 0 < x < 1.
5. The solid electrolyte according to claim 1, wherein R is Er, and the solid electrolyte exhibits a diffraction peak in the range of 2θ = 27.94° or more and 28.10° or less in X-ray diffraction analysis using CuKα radiation.
6. The solid electrolyte according to any one of claims 1, 2, and 5, wherein R is Er, M1 is Zr, and x satisfies 0 < x < 1.
7. A positive electrode, characterized in that It includes the solid electrolyte according to any one of claims 1 to 6, a positive electrode active material configured to exchange lithium ions with the electrolyte, and a surface on which the solid electrolyte and the positive electrode active material are disposed.
8. A secondary battery, characterized in that: It includes: The positive electrode according to claim 7; An electrolyte layer configured to be in contact with the surface and configured to exchange lithium ions with the positive electrode; and A negative electrode that contacts the opposite surface of the electrolyte layer and the surface side.
9. An electrolyte layer, characterized in that It includes a surface on which the solid electrolyte according to any one of claims 1 to 6 is disposed.
10. A secondary battery, characterized in that: It includes the electrolyte layer according to claim 9, a positive electrode configured to be in contact with the surface and to exchange lithium ions with the electrolyte layer, and a negative electrode that contacts the opposite surface of the surface of the electrolyte layer.
11. A solid electrolyte, characterized in that: It includes a boron oxide containing Li, an element R selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and an element M selected from the group consisting of Zr, Ce, and Sn.
12. The solid electrolyte according to claim 11, wherein the atomic concentration ratio [M] / [R] of the element M to the element R is 0.026 or more and 1.500 or less.
13. The solid electrolyte according to claim 12, wherein the atomic concentration ratio [M] / [R] is 0.111 or more and 0.290 or less.
14. A solid electrolyte, characterized in that: It includes a boron oxide containing Li, an element R selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, and an element M selected from the group consisting of Zr, Ce, and Sn. In the X-ray diffraction analysis using CuKα radiation, the solid electrolyte shows two diffraction peaks in the range where the diffraction angle 2θ is 27.4° or more and 29.0° or less, and the difference in diffraction angle 2θd between the higher-angle diffraction peak and the lower-angle diffraction peak is 0.43° or more.
15. A solid electrolyte, characterized in that: It comprises the general formula Li 6-x R 1-x M x (BO3)3 represented by oxide, In this formula, R is a rare earth element selected from the group consisting of Yb, Er, Ho, Tm, La, Nd, and Sm, M is an element selected from the group consisting of Zr, Ce, and Sn, and x is a real number satisfying 0 < x < 1.
16. The solid electrolyte according to claim 14, wherein in the X-ray diffraction analysis using CuKα radiation, the solid electrolyte shows two diffraction peaks in the range where the diffraction angle 2θ is 27.4° or more and 29.0° or less, and the difference in diffraction angle 2θd between the higher-angle diffraction peak and the lower-angle diffraction peak is 0.43° or more.
17. The solid electrolyte according to claim 15, wherein in the X-ray diffraction analysis using CuKα radiation, the solid electrolyte shows two diffraction peaks in the range where the diffraction angle 2θ is 27.4° or more and 29.0° or less, and the difference in diffraction angle 2θd between the higher-angle diffraction peak and the lower-angle diffraction peak is 0.43° or more.
18. The solid electrolyte according to any one of claims 11 to 17, wherein the element M contains Zr.
19. The solid electrolyte according to claim 18, wherein the element M further contains Ce.
20. The solid electrolyte according to any one of claims 11 to 17, wherein the element R contains multiple rare earth elements.
21. The solid electrolyte according to claim 20, wherein the multiple rare earth elements at least contain Yb.
22. The solid electrolyte according to claim 21, wherein the ratio of the concentration of the element other than Yb contained in the element R to the atomic concentration of the rare earth element R, ([R] - [Yb]) / [R], is 0.063 or more and 0.200 or less.
23. The solid electrolyte according to any one of claims 11 to 17, wherein the rare earth element R contains Yb, and in the X-ray diffraction analysis using CuKα radiation, the solid electrolyte shows a diffraction peak in the range where the diffraction angle 2θ is 28.07° or more and 28.20° or less.
24. The solid electrolyte according to claim 15, wherein the rare earth element R contains Yb, the M contains Zr, and x satisfies 0 < x < 1.
25. The solid electrolyte according to claim 15, wherein The rare earth element R contains Er, and in the X-ray diffraction analysis using CuKα radiation, the solid electrolyte shows a diffraction peak in the range where the diffraction angle 2θ is 27.94° or more and 28.10° or less.
26. The solid electrolyte according to claim 15, wherein the rare earth element R contains Er, the M contains Zr, and x satisfies 0 < x < 1.
27. A positive electrode, characterized in that The positive electrode active material comprises the solid electrolyte according to any one of claims 11 to 26, and a positive electrode active material configured to transfer lithium ions to and from the solid electrolyte. 28 . The positive electrode according to claim 27 , wherein the positive electrode has a surface on which the solid electrolyte and the positive electrode active material are arranged.
29. A secondary battery, characterized in that: It includes: The positive electrode according to claim 28; an electrolyte layer configured to be in contact with the surface and configured to transfer lithium ions to and from the positive electrode; and A negative electrode is in contact with a surface of the electrolyte layer opposite to the surface-contact side.
30. An electrolyte layer, characterized in that It comprises a surface on which the solid electrolyte according to any one of claims 11 to 26 is arranged.
31. A secondary battery, characterized in that: It comprises the electrolyte layer according to claim 30, a positive electrode configured to be in contact with the surface and to transfer lithium ions with the electrolyte layer, and a negative electrode in contact with a surface opposite to the surface of the electrolyte layer.
